Development of a measurement index of critical thinking in professional formation - Ospina Rave, Beatriz Elena; Brand Monsalve, Edinson Gabriel; Aristizabal Botero, Carlos Andrés (Investigación y Educación en Enfermería, 2017)
Objective. This research sought to construct and validate a measurement index of critical thinking (CT) in professional formation. Methods. Transversal, quantitative, test validation-type study. After reviewing scientific production in CT, which permitted defining the concept and its conceptual domains, a 65-item scale was constructed of closed questions on the analysis of cases evaluating CT. The scale was subjected to expert evaluation to then be applied to 53 undergraduate students (35 from nursing and 18 from sociology) to evaluate validity and reliability. Results. The 65-item scale has an explained variance of 61.3% and is comprised of five CT domains: inference, evaluation, argumentation, analysis, and interpretation. A Cronbach’s alpha coefficient of 0.61 was obtained. Conclusion. The scale proposed to assess students’ CT skills converges with concepts by known authors with the CT theory and is adequate for use as a CT measurement index in professional formation. How to cite this article: Ospina BE, Brand EG, Aristizabal CA. Development of a measurement index of critical thinking in professional formation. Invest. Educ. Enferm. 2017; 35(1):